Effect of Different Liner Materials on Elastohydrodynamic Lubrication of Oil-water Two-phase Lubricated Rolling Mill Oil Film Bearing - Wang Youqiang; Wang Tao; Xu Caihong; Wang Limei; Zhang Tonggang (Jixie chuandong)
Taking the rolling mill oil film bearing as the research object,the model of oil- water two-phase flow of elastohydrodynamic lubrication is established by using with thermal effect of the Reynolds equation. The effects of three common liner materials are compared on rolling mill oil film bearing lubrication property. Combining with the special working condition of rolling mill oil film bearing,the lubrication characteristic of oil- water mixture are analyzed under different water contents,spindle speed and rolling force. The results show that,the babbitt in three liner materials,the maximum and center pressure are minimum,whose the overall,center and minimum film thickness are maximum to be best for lubrication performance,while its maximum temperature is maximum to be best for heat dissipation. Therefore,selecting the babbitt as liner material is most suitable for oil film bearing. The oil watering with the increasing of water content,the maximum pressure is decreased,the inlet zone pressure and minimum film thickness are increased to be promoted lubrication performance. As the rotational speed increase,the maximum pressure is decreased,the inlet zone pressure and minimum film thickness are increased. As the rolling force increase,the maximum pressure is increased,the inlet zone pressure and minimum film thickness are decreased.